BREAKDOWN OF PEOPLE’S CONFIDENCE IN THE ORTHODOX CHURCH IN THE RUSSIAN EMPIRE IN THE LATE XIX – EARLY XX CENTURY (FOR EXAMPLE, SOUTH UKRAINE) - Tatarchenko О. V.; Tokalenko, P. O. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction: Russian Orthodox Church in the early twentieth century experienced a spiritual crisis that is associated with a reduction in the number of Orthodox believers. Not coincidentally, the first Russian revolution was decisive for the Orthodox Church with ideological point of view. The question of whom to support in the internal political conflict was not, however, were members of the clergy among the revolutionaries. Traditionally, most clergy supported the monarchical power and therefore the question: Why is the church did not remained at the side of the protesters, who defended the liberal aspirations of the Russian Empire is still relevant. Purpose: The authors try to investigate the causes of decline in the authority of the Orthodox Church in the early twentieth century and clarify the role of the clergy in the events of the first Russian revolution in the south of Ukraine. Results: Based on their study the authors argue that the peasantry and urban poor suddenly find themselves on the field of ideological struggle between the supporters of the official church and atheists. Moreover, it should be noted that atheists are often used unequivocal arguments against Church, referring to crimes in which the Russian Orthodox Church took part in the First Russian Revolution and emphasizing that the clergy despite it not got any punishment. Originality: The authors try to investigate the events of the Russian Revolution in southern Ukraine on the basis of documentary sources, reflecting society’s attitude to the Orthodox clergy, also analyzed literary works Ukrainian writers of the late nineteenth early twentieth century. Conclusion: Summarizing the results of support church the monarchy, the authors argue that the Russian Orthodox Church as a social institution in the Russian Empire finally lost the confidence of the population, openly taking anti-revolutionary position. For intellectuals church became synonymous of monarchism that identified with autocratic rule. It is no coincidence that the image of Orthodox priest associated with the policy of terror during the reaction to the liberal and radical revolutionary-minded intellectuals. Thus Orthodoxy was the reason for the division of society into supporters and critics of the Orthodox ideology.